2015
DOI: 10.1111/jre.12342
|View full text |Cite
|
Sign up to set email alerts
|

Are sickle cell anaemia and sickle cell trait predictive factors for periodontal disease? A cohort study

Abstract: SCT can act as a predictor for establishment of periodontal diseases. There was no correlation between SCA and periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Although a study reported no association between SCA and periodontal disease (de Carvalho, Thomaz, Alves, & Souza, 2016), we believe that iron overload induced by blood transfusion therapy can be a risk factor for the occurrence and progression of periodontal disease in this population. Moreover, only one clinical study has evaluated the deleterious effects of iron overload on periodontal tissues (Meuric et al, 2017).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although a study reported no association between SCA and periodontal disease (de Carvalho, Thomaz, Alves, & Souza, 2016), we believe that iron overload induced by blood transfusion therapy can be a risk factor for the occurrence and progression of periodontal disease in this population. Moreover, only one clinical study has evaluated the deleterious effects of iron overload on periodontal tissues (Meuric et al, 2017).…”
Section: Introductionmentioning
confidence: 54%
“…Radiographic images were taken on the day when periodontal evaluation was conducted and were analysed by three trained examiners (kappa interexaminer and intraexaminer = 0.83). Radiographs were obtained and processed in a standardized manner as described in a previous study (de Carvalho et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, no precedent can be found in the literature on the association between SCT and changes in tooth shape, size and periapex. Although this condition is considered asymptomatic, SCT may be a risk factor for adverse events in certain situations (de Carvalho et al., ; Tsaras et al., ). Evidence shows that individuals with SCT exposed to low oxygen conditions can exhibit changes linked to vaso‐occlusive events similar to those described in SCA (Goldsmith et al., ; Key & Derebail, ), thus increasing the occurrence of dental and bone changes.…”
Section: Discussionmentioning
confidence: 99%
“…Although individuals with SCT are considered asymptomatic, when exposed to low oxygen conditions, they may suffer vaso‐occlusion and potentially present clinical complications similar to SCA (de Carvalho, Thomaz, Alves, & Souza, ; Key & Derebail, ), such as trabecular bone changes (Gillis & West, ). However, population‐based studies that evaluated the associations of SCA and SCT with dental and bone changes were not found.…”
Section: Introductionmentioning
confidence: 99%
“…The highlights of these as they may pertain to older patients with SCD will be summarized in this review. Table 6 lists the dental comorbidities described in patients with SCD [106][107][108][109][110][111][112][113]. Caries are the most common dental comorbidity globally and in patients with SCD.…”
Section: Orofacial Comorbiditiesmentioning
confidence: 99%